2014
DOI: 10.1007/s12070-014-0785-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre-decannulation Peristomal Findings in Tracheostomized Cases and Their Effect on the Success of Decannulation

Abstract: Decannulating a patient on a tracheostomy is a procedure that has to be dealt with vigilantly. This study evaluated both external and telescopic/bronchoscopic findings at the peristomal level of subjects being considered for decannulation. The patients did not undergo any intervention after above observations and before attempting decannulation. Thereafter peristomal findings and their contribution towards failure to decannulate were correlated. Thirty subjects were studied prospectively, of whom 21 (70 %) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…We also found that 14 articles used objective examinations in the decannulation process, having five studies using nasolaringofibroscopia (11,18,20,22,31) , four using broncoscopia (20,27,28,35) , two using tomography (18,36) and three studies using swallowing videoendoscopy (15,18,26) . The use of the pulmonar (29) and manometry (31) function tests were less observed.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…We also found that 14 articles used objective examinations in the decannulation process, having five studies using nasolaringofibroscopia (11,18,20,22,31) , four using broncoscopia (20,27,28,35) , two using tomography (18,36) and three studies using swallowing videoendoscopy (15,18,26) . The use of the pulmonar (29) and manometry (31) function tests were less observed.…”
Section: Resultsmentioning
confidence: 83%
“…Three of the studies used medical records as a way of collecting data, and one study did not mention the members of the team. Luo et al (24) 44.57 4 17 X Berney et al (25) 47 15 29 X X X X Pandian et al (20) 58.07 18 39 X X X X Warnecke et al (26) 56.4 45 55 X X Hernández et al (27) 54.5 43 108 X X X Pryor et al (15) 53 44 82 X X X Cohen et al (22) 61.6 18 31 X X Mah et al (19) 55.1 144 249 X X X Zanata et al (9) 32.1 10 50 X Mathur et al (28) 22.67 12 18 X Kim et al (29) 47.6 7 55 ----Mitton et al (30) 52 41 65 X X X X Welton et al (16) 61 23 21 X X X X Pasqua et al (31) 64 21 27 ----Zanata et al (21) 53 4 16 X X Thomas et al (17) 71.4 36 86 X X X Tawfik et al (32) 48 57 38 ----Nakashima et al (33) 44.9 22 142 X Terra et al (34) 37.8 33 59 X X Schneider et al (35) 61.4 22 31 X X X Bianchi et al (11) 75 24 27 X X X Shrestha et al (36) 36 20 98 X X X -Budweiser et al (37) 70 46 120 ----Gundogdu et al (18) 29. Baseline disturbances data were also listed in the populations of each article (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations